Effects of Dietary Supplementation with Fish Scales-Derived Collagen Peptides on Skin Parameters and Condition: A Randomized, Placebo-Controlled, Double-Blind Study - Koizumi, Seiko; Inoue, Naoki; Shimizu, Maiko; Kwon, Chang-ju; Kim, Hwa-young; Park, Kyoung Sik (International journal of peptide research and therapeutics, 2018)
Fish scales-derived collagen peptides (CPs) are characterized by their specific amino acid composition with a high concentration of glycine, proline and hydroxyproline. These amino acids have been known to exert beneficial effects on human skin. The aim of the present study was to examine the effects of collagen peptides obtained from fish scales on changes in periorbital wrinkles, facial skin hydration, and skin elasticity in healthy women aged 30–60 years. In the present randomized, placebo-controlled, double-blind trial, 71 subjects consumed a 20 mL beverage containing 3000 mg of CPs or placebo once per day over 12 weeks. Significant decreases in periorbital wrinkles ( p < 0.05) were observed in the treatment group after 12 weeks of CPs ingestion compared to the control group. This study also demonstrated a consistent trend of enhanced facial skin moisture ( p < 0.001) and skin elasticity ( p < 0.001) by dietary intake of CPs without any side effects or adverse events. These findings indicate that fish-derived CPs hold great promise as a natural supplement with cutaneous anti-aging properties.